Effects of heat stress on posture transitions and reproductive performance of primiparous sows during late gestation. (February 2021) - Liu, Longshen; Tai, Meng; Yao, Wen; Zhao, Ruqian; Shen, Mingxia
Abstract: This study aimed to investigate the effects of heat stress on posture transitions of perinatal primiparous sows around the parturition period from 72 h prepartum to 24 h postpartum. The reproductive performance of sows was measured, and the relationship between posture transitions and reproductive performance was also analyzed. Ten primiparous sows were randomly assigned to thermoneutral (TN) (18–22 °C; n = 5) or heat stress (HS) (28–32 °C; n = 5) treatments. Posture transitioning, including the frequency of posture change, duration of dynamic posture (DP), and lateral lying with udder to the piglet creep box (PCB) during three periods (72 h prepartum, sub-partum, and 24 h postpartum, respectively), were recorded. Posture change frequency was significantly increased, starting from 24 h prepartum to the onset of farrowing in both the TN (P < 0.05) and HS (P < 0.01) groups. Moreover, the peak value of posture change frequency in the TN group was concentrated during the 12 h prepartum period, positively correlated with the quantities of head-first birth piglets and sub-partum duration, respectively. DP duration increased during the period of 24 h prepartum and then decreased sharply (P < 0.001 and P < 0.05 for TN and HS groups, respectively). The duration of facing the udder to the PCB increased during sub-partum and postpartum TN (P < 0.001). The duration of sub-partum (P < 0.05) and delivery time of single piglets (P < 0.01) in the HS group was prolonged, and piglets from the HS group had a lower weight gain than the TN group both at d10 (P < 0.001) and weaning time (P < 0.001). In conclusion, HS had obvious adverse effects on nursery behavior and reproductive abilities in perinatal primiparous sows, which resulted in poor growth performance of lactating piglets. Highlights: The effect of heat stress on posture transitions of perinatal sows were investigated. The delivery time of single piglet affected by heat stress. The effect of heat stress on reproductive performance of sows were investigated. Sows' posture transitions were related to the reproductive performance.